2021
DOI: 10.3390/plants10050842
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of African Soapy Saponin—Rich Plants for Possible Use in Communities’ Response to Global Pandemics

Abstract: Plants that exhibit foaming properties when agitated in aqueous solutions are commonly referred to as soapy plants, and they are used in different communities for washing, bathing, and hair shampooing. The frothing ability of these plants is attributed to saponins which are also well-documented to possess antimicrobial attributes. In the light of COVID-19, soap and hand hygiene have taken center stage. The pandemic has also revealed the low access to running water and commercial soaps in many marginalized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that plant part, tissue type, age, physiological state, and genetic profiles can affect the concentration of chemical constituents in plants, including saponins. Furthermore, the quantifiable amount of saponins also depends on the solvent used in the extraction [101].…”
Section: Saponin Concentrations In the Selected Plantsmentioning
confidence: 99%
“…Previous studies have shown that plant part, tissue type, age, physiological state, and genetic profiles can affect the concentration of chemical constituents in plants, including saponins. Furthermore, the quantifiable amount of saponins also depends on the solvent used in the extraction [101].…”
Section: Saponin Concentrations In the Selected Plantsmentioning
confidence: 99%
“…Bathing regularly, preferably twice a day (morning and night), with antiseptic soap and clean running water and regular washing of clothes with germ-killing detergents may kill SARS-CoV-2. 77) Regular dental hygiene during this pandemic and later is imperative; people with periodontal disease may be at an increased risk of severe outcomes from COVID-19 than the general population are. 78) A potential relationship between periodontal disease and COVID-19 has been established through two routes.…”
Section: Personal Care and Hygienementioning
confidence: 99%
“…During this pandemic, body and skin hygiene has been crucial. Bathing regularly, preferably twice a day (morning and night), with antiseptic soap and clean running water and regular washing of clothes with germ-killing detergents may kill SARS-CoV-2 [ 77 ].…”
Section: General Strategies For Maintaining a Healthy Lifestyle Durin...mentioning
confidence: 99%
“…Saponin is a secondary metabolite distributed in more than one hundred families of vascular plants (Kunatsa & Katerere, 2021;Rai et al, 2021). The different quantities of saponin may be isolated from various parts of plants (Kunatsa & Katerere, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Saponin is a secondary metabolite distributed in more than one hundred families of vascular plants (Kunatsa & Katerere, 2021;Rai et al, 2021). The different quantities of saponin may be isolated from various parts of plants (Kunatsa & Katerere, 2021). The utilization of plant-derived saponins should be considered, as their excellence of being safe and environmentally friendly, biodegradable, and renewable, as well as their pharmaceutical effects (Wisetkomolmat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%